Ecological studies and management of Vanessa cashmirensis on hop (Humulus lupulus) in dry temperate Himachal Himalayas - SOOD, A K; KASHYAP, N P (The Indian Journal of Agricultural Sciences, 2014)
Vanessa cashmirellsis Kollar (Nymphalidae: Lepidoptera) completes two-three overlapping generations annually during April-September in the Lahaul valley of Himachal Pradesh. But the second occurring during mid-June to July causes devastating damage to hop (Humulus lupulus L.) plantations. The peak of the pest activity occurred between the end of June and first week of July with the population of 59.3-90Alarvae/ vine during 1995-97. The population of V. cashmirensis was curtailed by predacious spiders, wasp and a larval-pupal ichneumonid parasitoid. V. cashmirensis completed the life cycle from egg to adult emergence in 37-44 days at 25Â°C. Persistent toxicity of six insecticides tested at three concentrations each against third instar caterpillars revealed that carbaryl (0.1 and 0.2%), cypermethrin (0.0075 and 0.015%), chlorpyriphos (0.04 and 0.08%) and deltamethrin (0.0025 and 0.005%) remained effective and superior to others even up to 21 days of application except the deltamethrin which lost its effectiveness after 15 days.